2018
DOI: 10.1007/s00586-018-5673-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical practice guidelines for the management of non-specific low back pain in primary care: an updated overview

Abstract: We identified 15 clinical practice guidelines for the management of low back pain in primary care. For diagnosis of patients with non-specific low back pain, the clinical practice guidelines recommend history taking and physical examination to identify red flags, neurological testing to identify radicular syndrome, use of imaging if serious pathology is suspected (but discourage routine use), and assessment of psychosocial factors. For treatment of patients with acute low back pain, the guidelines recommend re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
935
5
114

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,073 publications
(1,066 citation statements)
references
References 26 publications
12
935
5
114
Order By: Relevance
“…Although recent national guidelines came to divergent recommendations on the importance of opioids in the management of chronic low back pain (CLBP) (Oliveira et al, 2018), opioid analgesics are commonly used for CLBP in Europe and North America (Shaheed, Maher, Williams, Day, & McLachlan, 2016). The long-term use of opioids for chronic non-cancer pain contributed to the opioid crisis in North America with a parallel increase in prescriptions of opioids, their non-medical use and associated increased mortality (Ranapurwala, Naumann, Austin, Dasgupta, & Marshall, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although recent national guidelines came to divergent recommendations on the importance of opioids in the management of chronic low back pain (CLBP) (Oliveira et al, 2018), opioid analgesics are commonly used for CLBP in Europe and North America (Shaheed, Maher, Williams, Day, & McLachlan, 2016). The long-term use of opioids for chronic non-cancer pain contributed to the opioid crisis in North America with a parallel increase in prescriptions of opioids, their non-medical use and associated increased mortality (Ranapurwala, Naumann, Austin, Dasgupta, & Marshall, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…; Oliveira et al. ), with 84% of people in all age groups expected to experience LBP during their lifetime (Balagué et al. ; Ostelo, ).…”
Section: Introductionmentioning
confidence: 99%
“…Low back pain (LBP) is the main musculoskeletal disorder responsible for disability worldwide (Hoy et al 2014;Maher et al 2017;Hartvigsen et al 2018;Oliveira et al 2018), with 84% of people in all age groups expected to experience LBP during their lifetime (Balagu e et al 2012;Ostelo, 2018). A systematic review showed that approximately 12% of the general population are affected by LBP (Hoy et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical presentation of the hypermobile joint is multifactorial and requires a detailed assessment to guide clinical decision‐making . A comprehensive evaluation should assess for factors contributing to hypermobility related to a systemic disorder or several conditions with overlapping symptoms .…”
Section: Clinical Presentation and Assessment Of The Hypermobile Jointmentioning
confidence: 99%
“…Treatment goals for the hypermobile sacroiliac joint should address strength, flexibility, stabilization, restoration of normal neuromuscular lumbopelvic control, and correction of functional adaptive changes as well as pain reduction. These goals are best accomplished with multiple and integrative therapies …”
Section: Treatment Approaches For Joint Stabilizationmentioning
confidence: 99%